Effect of Age and Sex on the Physico-Chemical and Sensory Quality of Meat from Giriraja Birds - Kogilasan, D; Mandal, P K; Venugopal, S; Pal, U K; Kasthuri, S; Gawdaman, G (Journal of Meat Science, 2026)
The present study was envisaged to assess the effect of age and sex on the  physico-chemical and sensory quality of meat from Giriraja birds reared up to  12 weeks of age at weekly interval. A total of 100-day-old Giriraja chicks were  reared in the institution poultry farm up to 12 weeks of age as per standard  management practices. Birds were divided in to two groups viz., male (47  birds) and female (53 birds) after completion of 6 weeks of age. Six birds each  from male and female groups were slaughtered every week from 8 to 12 weeks  as per the standard procedures and meat samples were collected from breast  and thighs for meat quality and sensory analysis. In male Giriraja birds highly  significant (P
Keywords: Giriraja birds; Meat quality; Physcio-chemical quality; Sensory quality; Water holding capacity